College Student-Athletes in Career Development: A Comparison of Career Decision-Making, Role Salience, and Values - Patterson, Howard Y.; Wooten, Jr., H. Ray (My University, 2001)
Student athletes are faced with a variety of struggles not encountered by their non-athlete peers. Chief among these struggles are the development of a personal identity, socialization, and self worth that is separate and distinct from their athletic lives. Decisions regarding career choices arerelated to developmental success in identity formation and self-efficacy. Student-athletes at NCAA Division I schools have been found to be significantly different from non-athletes in their readiness to make career decisions.This investigation explored whether similar deficiencies existed with student-athletes at a small private NCAA Division II university. This study compared career decision-making, role salience, and values of student-athletes (n=53) and non-athletes (n=51). A demographic form and three instruments were used to collect the data. The Salience Inventory (SI), the Values Scale (VS), and the Career Development Inventory (CDI) were used. The data indicated that athletes and non-athletes at a Division II university tend to be similar in the areas ofcareer decision-making, planning, and role salience. Athletes did project higher life style and prestige scores. Higher life style scores indicate that athletes tended to value the opportunity to plan one's own activities and to live the way one wants to. Many athletes feel most of their time is controlled by others (e.g., coaches, practice, classes), as a result, time for leisure is a premium. Elevated prestige scores indicate that athletes value being acknowledged for their skills more than non-athletes. The prestige score may highlight a desire by athletes to not only be acknowledged for their athletic ability but appreciated for their contribution, role, and sacrifice to the team. The authors recommend athletes create a portfolio for career development.
Keywords: Division II; career development; identity; ethics; non-athlete students